A longitudinal study of intermaxillary and intraarch relationships from mixed to permanent dentition: A 4-year follow-up - Carneiro, Diego Patrik Alves; Moraes, Caroline Nogueira; de Menezes, Carolina Carmo [UNESP]; de Castro Meneghim, Marcelo; Vedovello, Silvia A.S. (Elsevier, 2025)
Introduction: This longitudinal study assessed the intermaxillary and intraarch relationships from mixed to permanent dentitions during a 4-year follow-up. Methods: The sample comprised 352 children evaluated for crowding, midline maxillary diastema, anterior spacing, overjet, overbite, and sagittal and transverse relationships in mixed (T1) and permanent (T2) dentition. Data between different time points were compared using McNemar and Bowker symmetry tests, with a significance level of 5%. Results: Of the 352 children evaluated over a 4-year follow-up period, significant changes were observed in the intraarch and intermaxillary relationships from T1 to T2. The intraarch relationship showed significant decreases in crowding (61.3%), maxillary midline diastema (74.3%), and anterior spacing (82.2%) (P <0.0001). Regarding the intermaxillary relationship, statistically significant changes were observed in the overjet (P = 0.003), overbite (P = 0.004), and anteroposterior (P <0.0001) and transverse relationships (P <0.0001). In addition, 43.1% of children had increased overjet at T1 and normal overjet at T2, 29.3% of children with a Class II relationship at T1 and Class I relationship at T2, 70.5% of children with posterior crossbite and normal transverse relationship at T2, and 73.9% of children with anterior open bite and normal overbite at T1 and average overbite at T2. Conclusions: Significant favorable changes in intraarch relationships were observed during the transition from mixed to permanent dentition. Children also show changes in intermaxillary relationships, with a potential improvement in occlusion of the permanent dentition.